Strategi Pengembangan SDM dalam Manajemen Pendidikan Islam - Khairul Anwar Deesaeh (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2025)
Human resource development (HRD) is a fundamental pillar in the management of Islamic education, especially in the era of globalization and the industrial revolution 4.0. Islamic educational institutions are required to produce graduates who are not only religious but also competent, ethical, and adaptive. This study aims to identify effective HRD strategies to improve the quality of Islamic educational institutions. The research employs a qualitative approach with data collected through interviews, observations, and documentation in several Islamic educational institutions. The findings reveal that strategies such as training, internships, scholarships, mentorship, collaboration, performance evaluation, spiritual development, technology implementation, and innovation play vital roles. The integration of Islamic values in recruitment, training, and career development is also crucial. However, challenges such as limited funding, lack of competent human resources, and insufficient leadership attention remain obstacles. This study emphasizes the need for innovation in HRD to overcome these barriers. It is expected that the findings provide practical solutions for Islamic educational institutions to achieve educational goals, produce quality graduates, enhance competitiveness, and contribute positively to society.